Development of Instant Soup Premix using Oyster Mushroom powder - Srivastava, Anuradha; Attri, B L; Verma, Shailja (Mushroom Research, 2019)
The present study was conducted to develop an instant soup premix utilizing oyster mushroom powder. Four formulations of mushroom soup mix containing varying proportions of mushroom powder (10-40%) were prepared by dry mixing of oyster mushroom powder, corn flour, milk powder, salt, sugar, black pepper and oregano and subjected to sensory and nutritional analysis.The soup mix formulation containing 20% oyster mushroom powder, 40% corn flour, 25 % milk powder, 8 % salt. 3 % sugar, 2 % black pepper, and 2 % oregano was found most acceptable based on sensory scores (7.69). The mushroom soup prepared with this soup mix was found rich in protein (11.79 g/100g), crude fiber (3.54 g/100g), minerals (12.6 g/100g), and low in fat (4.78 g/100g), carbohydrate (56.13 g/100g) and energy value (314.65 Kcal/100g). This mushroom soup can be prepared by mixing 50 g of soup mix in 750 ml water (15 times) and boiling for 2 minutes.